Influence of exercise on quantity and deformability of immune cells in multiple sclerosis - Proschmann, Undine; Shalchi-Amirkhiz, Puya; Andres, Pauline; Haase, Rocco; Inojosa, Hernán; Ziemssen, Tjalf; Akgün, Katja (Frontiers in Neurology, 2023)
Objective The study aimed to investigate the effect of exercise on immune cell count and cell mechanical properties in people with multiple sclerosis (pwMS) on different disease-modifying treatments (DMT) vs. healthy controls (HCs). Methods A cohort of 16 HCs and 45 pwMS, including patients with lymphopenia (alemtuzumab and fingolimod) as well as increased lymphocyte counts (natalizumab), was evaluated for exercise-mediated effects on immune cell counts and lymphocyte deformability. As exercise paradigms, climbing stairs at normal speed or as fast as possible and cycling were used, while blood samples were collected before, immediately, and 20 as well as 60 min post-exercise. Immune cell subtypes and lymphocyte deformability were analyzed using multicolor flow cytometry and real-time deformability cytometry. Results An increase in lymphocytes and selected subsets was observed following exercise in HCs and all pwMS on different DMTs. Patients with lymphopenia exhibited an increase in absolute lymphocyte counts and immune cell subsets till just below or into the reference range. An increase above the upper limit of the reference range was detected in patients on natalizumab. Exercise-induced alterations were observable even in low and more pronounced in high-intensity physical activities. Lymphocyte deformability was found to be only mildly affected by the investigated exercise regimes. Conclusion People with multiple sclerosis (PwMS) treated with alemtuzumab, fingolimod, and natalizumab respond to acute exercise with a comparable temporal pattern characterized by the increase of immune cell subsets as HCs. The magnitude of response is influenced by exercise intensity. Exercise-mediated effects should be considered when interpreting laboratory values in patients on immunomodulatory therapy. The impact of exercise on biophysical properties should be further elucidated.